Revision of the Oriental species of Polypedilum Kieffer (Diptera: Chironomidae) with their phylogenetic relationship - Mukherjee, Tuhar; Mukherjee, Bindarika; Hazra, Niladri (Zootaxa, 2020)
Imagines and pupae of new species Polypedilum (Pentapedilum) retusum are described from India. Three species, P. (Polypedilum) tamanigrum Sasa, 1983, P. (Pentapedilum) anale (Freeman, 1954), and P. (Tripodura) conghuaense Zhang, Song, Qi and Wang, 2016 with pupa are recorded firstly in the subcontinent. Hypopygia of P. (P.) ascium Chaudhuri, Guha and Das Gupta, 1981, P. (T.) conghuaense, P. (T.) lineatum Chaudhuri, Guha and Das Gupta, 1981 and P. (P.) nudiceps Chaudhuri, Guha and Das Gupta, 1981 are redescribed. Polypedilum (P.) exterflexum Hazra, Sanyal and Brahma, 2015, P. clavipennae Hazra, Sanyal and Brahma, 2015 and P. aduncum Konar and Hazra, 2017 are proposed here to transfer to the genus Stictochironomus Kieffer, 1919. Polypedilum (P.) insolitum Chaudhuri, Guha and Das Gupta, 1981 is here stated as junior synonym of Zavreliella marmorata (Wulp, 1859). In addition, some biogeographic and taxonomic remarks including DNA barcoding for selected species are given. Cladistic analysis of the Oriental species of Polypedilum Kieffer is made to hypothesise their possible relationship. A new dichotomous key of the Oriental species of Polypedilum is presented here.